Intestinal microbiome characterization of adult Brazilian men with psoriasis compared to omnivore and vegetarian controls - Polo, Tatiana Cristina Figueira [UNESP]; Lai, Mariana Righetto de Ré [UNESP]; Miot, Luciane Donida Bartoli [UNESP]; Bento, Giovana Fernanda Cosi [UNESP]; Silva, Márcia Guimarães da [UNESP]; Marques, Silvio Alencar [UNESP]; Miot, Hélio Amante [UNESP] (Elsevier, 2023)
Background: Psoriasis is a chronic inflammatory disease associated with systemic inflammation and comorbidities. Changes in the composition of the intestinal microbiome are involved in the pathogenesis of inflammatory diseases and metabolic syndrome. Characterizing the intestinal microbiome of patients with psoriasis may be relevant for the understanding of its clinical course and comorbidity prevention. Objective: To characterize the intestinal microbiome of men with psoriasis compared to omnivore and vegetarian controls (without psoriasis). Method: Cross-sectional study of 42 adult males: 21 omnivores with psoriasis; and controls: 14 omnivores and 7 vegetarian individuals. The characterization of the intestinal microbiome was performed by metagenomic analysis. Serum levels of lipopolysaccharide-binding protein (LPB) and C-reactive protein (CRP) were evaluated. Results: The groups differed from each other regarding nutritional aspects and microbiome; individuals with psoriasis had a higher consumption of protein and lower consumption of fibers. Levels of LPB, CRP, and the Firmicutes/Bacteroidetes ratio were higher in the group with psoriasis than in the vegetarian group (p < 0.05). The genera Prevotella, Mogibacterium, Dorea, Bifidobacterium and Coprococcus, differed in the group with psoriasis compared to vegetarians; the genera Mogibacterium, Collinsella and Desulfovibrio differed from omnivores. A microbiome pattern linked to psoriasis (plsPSO) was identified, which was associated with higher LPB levels (rho = 0.39; p = 0.02), and lower dietary fiber intake (rho = −0.71; p < 0.01). Study limitations: Only adult men were evaluated. Conclusion: A difference was identified in the intestinal microbiome of adult men with psoriasis when compared to healthy omnivores and vegetarian controls. The identified microbiome pattern was correlated with dietary fiber intake and serum levels of LPB.
Keywords: Diet; Gastrointestinal microbiome; Microbiota; Obesity; Psoriasis; Vegetarian diet; Western diet